Factors supporting youth recruitment for terrorist organisations in Africa: the case of Al-Shabab in Eastern Africa for the period of 2010-2020 - Lutywantsi, P. G. (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMil)--Stellenbosch University, 2023.